MENYELAMI HARAPAN DI TENGAH BAYANG-BAYANG KERESAHAN KERJA (Studi Pada Kantor Sekretariat Daerah Kabupaten Grobogan) - Pradana, Johan; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2021)
ABSTRACT The contract system in terms of employment is often associated with various weaknesses and problems, relating to work relations such as low wages, limited benefits, no job security, and many more. This system also has the potential to cause losses from the workers side and more profits from the employers side. This study aims to understand and find out how the working conditions experienced by contract workers in government agencies are often referred to as